Educational Technologies, Social Skills and Decision Making in University Students - Melgar Begazo, Arturo Eduardo (2019)
The objective of this research was to determine the relationship between educational technologies, social skills and decision making in university students of the Industrial Engineering School from a private university in Lima. This study was basic, its design was non-experimental and cross-sectional. The population was composed of 80 students. The survey was used as a technique and the questionnaire was used as its instrument. The questionnaire had Likert Scale questions. The results allowed determining that there is a significant relationship between educational technologies, social skills and decision making, with a significance lower than .05.